Mediasi Penal: Suatu Pilihan Konsep Perdamaian dalam Sistem Peradilan Pidana - Ismawati, Sri; Azizurrahman, Sy. Hasyim; Herlina, Herlina; Hertinia, Mega Fitri; Itasari, Endah Rantau (Universitas Negeri Malang, 2022)
This study analyzed the urgency and construction of penal mediation in the criminal justice system. The method used in this study was the normative juridical method with a doctrinal legal approach. The urgency of penal mediation in the criminal justice system was caused by the paradigm of retributive law enforcement, the limitations of criminal law, and the shift in the purpose of punishment. The construction of penal mediation in the criminal justice system was divided into two: penal mediation inside and outside the court. The settlement mechanism for penal mediation in court was carried out by giving authority to law enforcement officials to carry out the mediation process. The settlement mechanism for penal mediation outside the court could be left to the choice agreed upon by all parties involved in the settlement of criminal cases.This study analyzed the urgency and construction of penal mediation in the criminal justice system. The method used in this study was the normative juridical method with a doctrinal legal approach. The urgency of penal mediation in the criminal justice system was caused by the paradigm of retributive law enforcement, the limitations of criminal law, and the shift in the purpose of punishment. The construction of penal mediation in the criminal justice system was divided into two: penal mediation inside and outside the court. The settlement mechanism for penal mediation in court was carried out by giving authority to law enforcement officials to carry out the mediation process. The settlement mechanism for penal mediation outside the court could be left to the choice agreed upon by all parties involved in the settlement of criminal cases.